2015
DOI: 10.1177/1479164115610469
|View full text |Cite
|
Sign up to set email alerts
|

Role of myosin light chain and myosin light chain kinase in advanced glycation end product–induced endothelial hyperpermeability in vitro and in vivo

Abstract: We have previously reported that advanced glycation end products activated Rho-associated protein kinase and p38 mitogen-activated protein kinase, causing endothelial hyperpermeability. However, the mechanisms involved were not fully clarified. Here, we explored the role of myosin light chain kinase in advanced glycation end product-induced endothelial hyperpermeability. Myosin light chain phosphorylation significantly increased by advanced glycation end products in endothelial cells in a time-and dose-depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…We also observed that in the absence of overt dementia pathology, both circulating and brainderived EVs from hypoperfused mice contain proteins already implicated in neuronal atrophy, neuroinflammation, neurotoxicity and maintenance of brain tissue integrity, including hippocalcin, neurofascin, NCAM1 and MOG. These findings indicate that hypoperfused mice exhibit key features of AD, including BBB hyperpermeability (33,54,71), BBB-associated neuroinflammation (16,37,73), associated amyloid-β and tau neurotoxicity (3,51) and impaired lipid metabolism (52). Our findings further indicate that brain EVs incorporate both mediators of neuroprotection and hallmarks of neuronal damage, consistent with the concept that these vesicles act as a "doubled-edged sword" in AD (6), and shed important new light on specific protein mediators that might contribute to this functional dichotomy.…”
Section: Discussionmentioning
confidence: 84%
“…We also observed that in the absence of overt dementia pathology, both circulating and brainderived EVs from hypoperfused mice contain proteins already implicated in neuronal atrophy, neuroinflammation, neurotoxicity and maintenance of brain tissue integrity, including hippocalcin, neurofascin, NCAM1 and MOG. These findings indicate that hypoperfused mice exhibit key features of AD, including BBB hyperpermeability (33,54,71), BBB-associated neuroinflammation (16,37,73), associated amyloid-β and tau neurotoxicity (3,51) and impaired lipid metabolism (52). Our findings further indicate that brain EVs incorporate both mediators of neuroprotection and hallmarks of neuronal damage, consistent with the concept that these vesicles act as a "doubled-edged sword" in AD (6), and shed important new light on specific protein mediators that might contribute to this functional dichotomy.…”
Section: Discussionmentioning
confidence: 84%
“…In addition, the nucleus receives the activated NF-B p65 subunit, which initiates MLCK transcription and increases MLCK protein production. Interestingly, LPS stimulation of intestinal epithelial cells simulates the production of inflammatory factors in vivo, further disrupting the intestinal epithelial barrier and activating the release of inflammatory factors [ 69 ]. Alternatively, the TJ protein expression is disrupted by MLCK protein activation, which disrupts TJ protein structure and function [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Aging is considered as a major risk factor for microvascular dysfunction and hyperpermeability [ 143 ]. ML7 has been reported to alleviate advanced glycation end products-induced microvascular hyperpermeability in vivo [ 144 ], demonstrating the potential to protect against aging. Drosophila suppression of actomyosin contractility via protein kinase A-mediated regulation of MLCK activity has shown to be required for blood–brain barrier integrity [ 145 ].…”
Section: Discussionmentioning
confidence: 99%